(untitled) (Research, Society and Development, 2021)
Piperine is the main alkaloid amide extracted from the seeds of Piper ningrum L., has biological properties of the type: antimicrobial, anti-inflammatory, bioavailability of drugs. Zinc-Eugenol Oxide (ZOE) together, constitute the cements widely used in dentistry as a temporary dressing. This study aimed to verify the antimicrobial action of the composition from Piperine and ZOE. The agar diffusion method with well drilling was used in OZE/PIP solutions with different percentages of piperine: 4, 5, 10 and 20%. The reference strains were Staphylococcus aureus, Streptococcus mutans, Escherichia coli, Pseudomonas aeruginosa, Enterococcus faecalis and Candida albicans. The concentration of piperine 4% showed the greatest inhibition halos when tested with the strains P. aeruginosa (29mm), S. aureus (26mm), E. coli (24mm). The increase in the concentration of piperine in the composition did not influence the sizes of the inhibition halos, except for S. mutans that formed a 15 mm halo in the composition with 5% piperine and Enterococcus that formed 14 mm halos with 5 and 20% piperine. The composition proved to be efficient, in its different proportions, in combating more resistant microorganisms (S. aureus), and in the most common microorganisms in the oral cavity (S. mutans, C. albicans).